UMA LEITURA DO PROCESSO DE ESCRITURA EM SALA DE AULA: CONSIDERAÇÕES EM TORNO DO REAL, SIMBÓLICO E IMAGINÁRIO - Felipeto, Cristina (2010)
This work intends to articulate the singularities involved in the process of writing in the school and triad Real, Symbolic and Imaginary proposed by Lacan (1985). We´ll analyze episodes where students produce their writing through 2 opposing forces: the Imaginary one, aiming a Unity, and the Real one affecting this writing from an unexpected.